Active Role of the Community in Increasing Sustainable Tourism in Sibolangit Village - Siringoringo, Yan Batara Putra; Nababan, Esther Sorta Mauli; Hasibuan, Citra Dewi; Sitepu, Suryati; Sujatmoko, Koko (Jurnal Mitra Prima, 2025)
Sibolangit Village is known as a tourist village because it has a lot of natural potential that can be developed into a tourist destination in Deli Serdang Regency. Some of the tourism potential in Sibolangit Village includes the Taman Wisata Alam Sibolangit, Tangga Seribu, Uruk Sikuda-kuda, Taman Pekabar Injil Pertama GBKP, Goa Sejarah, Pemandian Alam Sibolangit. However, the management of tourist attractions in Sibolangit Village is not yet optimal because human resources in terms of expertise and skills in the field of tourism are still minimal, causing the tourist attraction to be unattractive and ultimately the number of visitors does not experience a significant increase. Carry out community service activities by holding training to improve skills in managing tourism businesses, marketing and customer service in Sibolangit Village. This training also covers aspects of sustainability, making the community the guardian and custodian of local heritage. Apart from that, a Tourism Awareness Group (Pokdarwis) will be formed as a representative of the Sibolangit Village community in developing tourism.